Making Education Game to Choose Healthy Snacks for Children - Vania Wahyu Febriani; Brenda Chandrawati; Dwiyoga Widiantoro (SISFORMA, 2016)
One of the learning media is games. Games that can be used as a learning tool can be called as education games. Because children like games, games can make positive effect for them. Children can study while playing games.Education game that have theme about snacks for children still rarely be found. Unfortunately, children from elementary school have a habit to buy and eat snacks without paying attention to snacks hygiene and health. With this reason, education about choosing hygiene and healthy snack for children made. The aim for this games is to make children more careful about choosing snacks that they will eat later.In this paper, there will be explained about how to make education game about snacks and with proof if this game can be used as an education tool to educate children about snacks.